Preference utilisation and customs data: The missing pieces of the FTA puzzle - Anna Jerzewska; Nicolas Köhler (European Centre for International Political Economy (ECIPE), 2019)
Even though free trade agreements (FTAs) have proliferated for several decades, researchers still don't fully understand their effects. In the wake of mega-regional trade deals, many governments are now interested in evaluating the effectiveness of their existing commitments and the benefits they have brought for business. It is, therefore, more important than ever to understand how FTAs are applied and to pinpoint any issues in their design or implementation. Unfortunately, policymakers have only a limited understanding of FTA utilisation and often rely on incomplete data and estimates. As the political momentum for greater transparency on trade agreements is increasing, there is a pressing need to create a centrally-held, WTO-driven and standardised database of utilisation data for trade agreements. This would allow for a more systematic review of how current trade agreements have been implemented and are applied.
Keywords: 330